If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 14) = -3x + -33 Reorder the terms: 5(14 + x) = -3x + -33 (14 * 5 + x * 5) = -3x + -33 (70 + 5x) = -3x + -33 Reorder the terms: 70 + 5x = -33 + -3x Solving 70 + 5x = -33 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 70 + 5x + 3x = -33 + -3x + 3x Combine like terms: 5x + 3x = 8x 70 + 8x = -33 + -3x + 3x Combine like terms: -3x + 3x = 0 70 + 8x = -33 + 0 70 + 8x = -33 Add '-70' to each side of the equation. 70 + -70 + 8x = -33 + -70 Combine like terms: 70 + -70 = 0 0 + 8x = -33 + -70 8x = -33 + -70 Combine like terms: -33 + -70 = -103 8x = -103 Divide each side by '8'. x = -12.875 Simplifying x = -12.875
| 8=3(v-4)-8v | | c+14=c | | x^2-3x+1=2-3x | | (5b-9)=(8-2b) | | -4y-3(-7y-3)=-7-8(1-y) | | b^2-2=0 | | 2a+a+36=180 | | 7/8=21/n | | (6a-24)=3a | | x/3-4=-20 | | 5(x-14)=33 | | 3k-6k=12 | | 2a=a+36 | | 2x+5x+x= | | -b+3b=-8 | | (43-3w)=(w+9) | | 5x-15=3x+15-2x | | -4(-x-9)+5=-(-5x-4)-2 | | 0.06=0.04+y+0.04y | | 6x+12=8x+24 | | 6*2*3*2/(16/4) | | 12=3k-6k | | 3c-43=4C-64 | | 2+5s=2 | | 7(-3)2= | | 7s=s+96 | | f(12)=3x-3 | | 8k=5k | | -1x=23 | | x+7+2x+13=4x+2 | | 8k=5j | | F(12)=12 |